An antigenic peptide inducing cross-reacting antibodies inhibiting the interaction of Streptococcus mutans PAc with human salivary components. - Senpuku, H (1995)
A 190-kDa surface protein antigen (PAc) of Streptococcus mutans, in particular the A region of this molecule, may be implicated in the induction of dental caries via an interaction with salivary components. For this reason, it was probably used successfully as an antigenic component for experimental vaccination to prevent dental caries in animals. While developing a synthetic peptide vaccine for dental caries, as reported herein, we have identified a unique peptide, TYEAALKQYEADL, as a candidate vaccinal immunogen. The amino acid sequence of this peptide completely corresponds to the sequence of a B-cell epitope in the A region of PAc and additionally contains its own T-cell epitope for B10.D2 mice within the molecule. This peptide strongly induces the production of only cross-reacting antibodies against PAc. In addition, as demonstrated by surface plasmon resonance analysis using the BIAcore system, these cross-reacting antibodies inhibit approximately 50% of the binding of fluid-phase salivary components to immobilized recombinant PAc.